2015
DOI: 10.1111/jog.12693
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tissue adequacy for histologic examination from Ipas MVA plus and Wallach Endocell in women with abnormal uterine bleeding

Abstract: MVA was comparable to Endocell in terms of tissue adequacy. Moderate to severe pain was experienced significantly more in the MVA group; however, the requirement of pain treatment was not significantly different between the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Previous studies have indicated that the performance of endometrial sampling is as good as those of dilatation and curettage (D&C) or manual vacuum aspiration. 4 , 5 In cases of postmenopausal bleeding, endometrial sampling has been shown to have a sensitivity of 90% and specificity of 99%–100% for diagnosing endometrial hyperplasia or endometrial cancer with D&C or hysteroscopy with biopsy as a reference standard. 6 A previous systematic review found moderate agreement with regard to tumor grade between endometrial sampling and final pathology from hysterectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the performance of endometrial sampling is as good as those of dilatation and curettage (D&C) or manual vacuum aspiration. 4 , 5 In cases of postmenopausal bleeding, endometrial sampling has been shown to have a sensitivity of 90% and specificity of 99%–100% for diagnosing endometrial hyperplasia or endometrial cancer with D&C or hysteroscopy with biopsy as a reference standard. 6 A previous systematic review found moderate agreement with regard to tumor grade between endometrial sampling and final pathology from hysterectomy.…”
Section: Introductionmentioning
confidence: 99%
“…However, MVA is not yet widely used due to limitation of supporting data. 16,17 Previous studies found similar tissue adequacy and similar histopathologic finding between MVA and uterine curettage. [18][19][20][21] Moreover, MVA was reported to have 86.4-96% sensitivity and 100% specificity for diagnosing endometrial pathology.…”
Section: Introductionmentioning
confidence: 72%
“…In our study, tissue adequacy identified by pathologist was 95.4% from endometrial cell sampler and 86.8% from MVA, which was statistically significantly different between methods. Previous studies reported 85-98% tissue adequacy from endometrial sampling devices [5][6][7]10,14,17,23 and 81-99% from MVA. [17][18][19]23,26 This difference in tissue adequacy between methods among studies could result from different factors, such as study design, the types of devices used, the characteristics of study participants, and differences in the level of operator experience.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study in Thailand for comparison of MVA versus Pipelle device shows better tissue adequacy in pipelle group (85.6% versus 81.1%). The study also highlighted higher difficult procedure with MVA (27.0% versus 14.4%) and significantly higher moderate to severe pain with MVA (60.7% versus 19.5%) (6). In the current study all the samples including the 24 repeat samples were taken using MVA which might have exaggerated inadequate sample.…”
Section: Discussionmentioning
confidence: 88%